Comparative Genomics and Evolutionary Analysis of RNA-Binding Proteins of the CsrA Family in the Genus Pseudomonas - Sobrero, Patricio Martín; Valverde, Claudio (Frontiers in Molecular Biosciences, 2020)
Gene expression is adjusted according to cellular needs through a combination of mechanisms acting at different layers of the flow of genetic information. At the posttranscriptional level, RNA-binding proteins are key factors controlling the fate of nascent and mature mRNAs. Among them, the members of the CsrA family are small dimeric proteins with heterogeneous distribution across the bacterial tree of life, that act as global regulators of gene expression because they recognize characteristic sequence/structural motifs (short hairpins with GGA triplets in the loop) present in hundreds of mRNAs. The regulatory output of CsrA binding to mRNAs is counteracted in most cases by molecular mimic, non-protein coding RNAs that titrate the CsrA dimers away from the target mRNAs. In γ-proteobacteria, the regulatory modules composed by CsrA homologues and the corresponding antagonistic sRNAs, are mastered by two-component systems of the GacS-GacA type, which control the transcription and the abundance of the sRNAs, thus constituting the rather linear cascade Gac-Rsm that responds to environmental or cellular signals to adjust and coordinate the expression of a set of target genes posttranscriptionally. Within the γ-proteobacteria, the genus Pseudomonas has been shown to contain species with different number of active CsrA homologues and of molecular mimic sRNAs. Here, with the help of the increasing availability of genomic data we provide a comprehensive state-of-the-art picture of the remarkable multiplicity of CsrA lineages, including novel yet uncharacterized paralogues, and discuss evolutionary aspects of the CsrA subfamilies of the genus Pseudomonas, and implications of the striking presence of csrA alleles in natural mobile genetic elements (phages and plasmids).